2001
DOI: 10.1260/0263617011493953
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Heavy Metal Removal in a Biosorption Column

Abstract: Column kinetics for metal removal could be described more adequately by a modified dose–response model than by the Thomas model or Bohart–Adams model conventionally used. The new empirical model can be used either in a linearized form or a non-linearized form. Use of the model minimizes the error resulting from use of the Thomas model, especially at lower or higher time periods of the breakthrough curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
186
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(197 citation statements)
references
References 6 publications
5
186
0
6
Order By: Relevance
“…This model was initially developed for pharmacology studies and recently used to describe adsorption of metals in some cases (Yan et al, 2001;Senthilkumar et al, 2006;Araneda et al, 2011). The modified dose-response model can be written as …”
Section: Modified Dose-response Modelmentioning
confidence: 99%
“…This model was initially developed for pharmacology studies and recently used to describe adsorption of metals in some cases (Yan et al, 2001;Senthilkumar et al, 2006;Araneda et al, 2011). The modified dose-response model can be written as …”
Section: Modified Dose-response Modelmentioning
confidence: 99%
“…One of the aims of these column studies was to achieve maximum capacities of a sorbent under specific boundary conditions. These capacities are needed to design full-scale systems for stormwater treatment (e.g., amount of sorbent and service life) [45]. The design of a full-scale system requires the prediction of the concentration-time profile or the breakthrough curve using lab-scale experiments.…”
Section: Column Experimentsmentioning
confidence: 99%
“…These removal capacities are important because they are needed to design full-scale systems for stormwater treatment (e.g., type and amount of sorbent, ratio of drainage area to filter area, or service life) [45]. For realistic stormwater runoff concentrations (2.5 mg/L and 5.0 mg/L) in batch experiments, all filter materials exhibited approximately 100% removal (with the exception of anthracite) and, therefore, achieved the same capacities (0.06 mg/g for Cu and Ni, 0.12 mg/g for Zn).…”
Section: Comparison Of Batch and Column Experiments Capacitiesmentioning
confidence: 99%
“…This model was proposed for the description of heavy metal biosorption in columns [16]. It is has been recently employed in other studies and it is referred as being commonly used to describe different processes in pharmacology.…”
Section: B Adsorption Testsmentioning
confidence: 99%
“…Yan and his co-workers [16] observed that use of this model minimizes the error resulting from the use of the Thomas model, especially at lower or higher time periods of the breakthrough curve. However, the parameters in this model have no physical significance and hence cannot be evaluated accordingly.…”
Section: B Adsorption Testsmentioning
confidence: 99%